Mental Health, Environmental, and Socioeconomic Geographic Factors of Severe Drug Addiction: Analysis of Rehabilitation Center Data in Indonesia - Wijaya Dewabhrata; Abdilah Ahsan; Adrianna Bella; Nadira Amalia; Dian Kusuma; Yuyu Buono Ayuning Pertiwi (SAGE Publishing, 2023)
Background: A growing number of recent literatures have attempted to document the factors related to drug use in different contexts, but limited studies analyzed the factors related to patient's severity level. Objective: We aimed to examine the correlates of behavioral, environmental, socioeconomic, geographic factors, and severe drug addiction. Methods: We used a sample of 6790 people who use drugs (PWUD) from rehabilitation centers during 2019 to 2020 in Indonesia. Data were obtained from Drugs Rehabilitation Information System (SIRENA) by the Indonesian National Narcotics Agency (BNN) during 2019 to 2020. SIRENA used the adapted version of WHO's Addiction Severity Index (ASI), which assesses patient's addiction severity level and relevant factors. A composite of the ASI factors is classified as "poor" or "serious" if its score is 4 or higher. The data was analyzed using logistic regression model to estimate correlations of severe drug addiction. Results: We found a high prevalence (65.08%) of our sample reported having severe drug addiction, which needed intervention and support. Poor psychiatric condition (OR = 4.02, CI: 2.97-5.44), serious work-related issue (OR = 2.10, 1.75-2.51), poor medical condition (OR = 2.01, 1.32-3.06), and serious family and social problems (OR = 2.56, 2.15-3.05) were significantly associated with severe drug addiction. Male users had higher odds of severe drug addiction (OR = 1.81, 1.55-2.20), compared to female counterparts. Patients in urban areas had higher odds of severe drug addiction (OR = 1.19, 1.1-1.3) than those in rural. Those in less developed regions (eg, Sumatera, Kalimantan, and Sulawesi) had higher odds of severe drug addiction (OR = 2.33, 1.9-2.9), compared to those in the most developed region (eg, Java and Bali). Conclusion: This evidence can help policymakers in refining the harm reduction policies in Indonesia and other countries with similar settings.